Journeys Home Research Report No. 1 - July 2012 - Johnson, G; Scutella, R; Wooden, M; Tseng, Y; Moschion, J (My University, 2012)
A key finding is that respondents’ housing situation appears to vary considerably over time. At the first interview half of the participants were in what we consider to be stable housing, a quarter were in more marginal living arrangements and 24 percent were homeless. However, when we examine homeless experiences in the six month prior to the first survey we find that 50 percent of the JH participants had been homeless. Almost all participants (94%) had reported an experience of homelessness at some stage in their lives. We also find some early indications that many respondents are cycling in and out of homelessness over their lifetimes, and spending considerable amounts of their lifetimes in an unstable housing situation. Almost half (49.7%) of respondents reported that they had spent at least a year homeless in total over their life and 23 percent had spent four or more years homeless. While we suspect that the JH sample may be better at capturing persons experiencing either ‘episodic’ or ‘chronic’ forms of homelessness, a plausible alternative is that long-term homelessness is more common than previously thought. Half of the participants had their first experience of homelessness at a young age (under 18) and just under three quarters had their first experience before they turned 25. We find evidence supporting the notion that people who first experience homelessness at a young age are more likely to experience persistent homelessness. Also, by far the most common reason reported for first becoming homeless was family breakdown and/or conflict. In contrast, a relatively low rate of respondents reported mental illness and substance abuse as major factors leading to their first homeless experience.
Keywords: Health -- Addictive behaviours; Disadvantage; Health -- Mental; Children -- Adolescents and youth; Life Events; Disadvantage, adversity and resilience; Health and wellbeing; Adolescents and youth; Disadvantage; Health; Children; Life Events; Mental; Addictive behaviours; Adolescents and youth; Adolescents and youth; Adversity and resilience; Dsiadvantage, adversity and resilience; Health and wellbeing